Pengaruh dan Efektivitas Metode Praktikum Terhadap Hasil Belajar Siswa pada Mata Pelajaran IPA Materi Makanan dan Nutrisi Kelas VIII B SMP Negeri 3 Segedong Kabupaten Mempawah - Andriono, Eko; Maria S, Haratua Tiur; Karolina, Venny; Kurniawan, Yudi (Jurnal Ilmiah Wahana Pendidikan, 2024)
This method provides direct experiences to students through practical activities aimed at allowing them to feel and understand concepts authentically. Previous research has shown that the practicum method is effective in improving students' understanding and learning outcomes in various learning contexts, such as biology and natural sciences. Additionally, this method has proven to increase students' learning motivation, including in online learning. Therefore, this study aims to evaluate the effectiveness of the practicum method on students' learning outcomes in the subject of natural sciences, specifically focusing on the topic of food and nutrition in class VIIIB at SMP Negeri 3 Segedong, Mempawah Regency. The research method employed is an experiment using paired-sample t-test to measure significant differences between pre-test and post-test scores. The results indicate a significant influence from the implementation of the practicum method on the topic of food and nutrition in the classroom. Data analysis, including normality tests and paired-sample t-tests, indicates that the data is normally distributed, and there is a significant difference between pre-test and post-test scores. Furthermore, the measurement of the effectiveness of the practicum method using N-Gain shows an effectiveness level of 57.8968, which can be concluded as reasonably effective. This research provides insights into the utilization of the practicum method in achieving the goals of natural sciences education, specifically in the context of food and nutrition. These findings can serve as a valuable reference for educators in choosing effective teaching methods to enhance students' learning outcomes